The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.3904/kjm.2014.86.3.298
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Electrocardiography Changes and Clinical Manifestations in Scrub Typhus in a Single Center

Abstract: The mechanism of electrocardiography (ECG) changes in patients with scrub typhus is still not clear. Orientia tsutsugamushi causes vasculitis in scrub typhus patients, which result in non-specific damage to the heart. However, serious damage to myofibril of the heart is not accompanied. Thus, chronic cardiac sequelae are rare. In addition to myocarditis, a variety of cardiac complications such as myocardial infarction, pericarditis have been reported. Additional research is needed to clarify the main mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Moreover, as the mean age of patients with scrub typhus in the study from Thailand was 39 years [10], influences related to age or underlying disease would likely explain the observed differences in the frequency of ECG abnormalities. 12 Atrial fibrillation was the most commonly observed type of arrhythmia observed in patients with scrub typhus. In Korea, the reported prevalence rates of Afib were 0.7% in people aged ³ 40 years, 2.1% in people aged ³ 65 years, and 4.0% in people aged ³ 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as the mean age of patients with scrub typhus in the study from Thailand was 39 years [10], influences related to age or underlying disease would likely explain the observed differences in the frequency of ECG abnormalities. 12 Atrial fibrillation was the most commonly observed type of arrhythmia observed in patients with scrub typhus. In Korea, the reported prevalence rates of Afib were 0.7% in people aged ³ 40 years, 2.1% in people aged ³ 65 years, and 4.0% in people aged ³ 80 years.…”
Section: Discussionmentioning
confidence: 99%